Choice of a Procedure for Optimizing Positive End-Expiratory Pressure in Patients with Acute Respiratory Distress Syndrome - A. V Vlasenko; V. V Moroz; V. N Yakovlev; V. G Alekseyev; N. N. Bulatov (Общая реаниматология, 2012)
Objective: to study the clinical efficiency of escalation and de-escalation procedures for optimizing positive end-expiratory pressure (PEEP) during mechanical ventilation (MV) in patients with acute respiratory distress syndrome (ARDS) resulting from direct and in indirect damaging factors. Subjects and methods. During a prospective study, 46 examined patients (30 men, 16 women; their age was 21 to 67 years) with ARDS of different genesis were divided into 2 groups: 1) 22 patients (14 men and 8 women) in whom the causes of ARDS were direct damaging factors: gastric content aspiration, blunt chest injury with lung contusion, and acute bilateral bacterial pneumonia; 2) 24 patients (16 men and 8 women) in whom the causes of ARDS were indirect damaging factors: abdominal sepsis, severe nonthoracic injury, and acute massive blood loss. In Groups 1 and 2, the efficiency of the escalation and de-escalation procedures for PEEP optimization was compared during controlled MV with a managed object. Results. In the patients with ARDS caused by direct damaging factors, the escalation procedure for PEEP optimization was more effective than the de-escalation one. In those with ARDS caused by indirect damaging factors, the de-escalation procedure for PEEP optimization was more effective than the escalation one. Conclusion. It is expedient to use a differential approach to choosing an escalation or de-escalation procedure for PEEP optimization in patients with ARDS induced by direct and indirect damaging factors. Key words: acute respiratory distress syndrome; direct and indirect damaging factors; mechanical ventilation; positive end-expiratory pressure; escalation procedure for PEEP optimization; de-escalation procedure for PEEP optimization; lung opening maneuver.